(a) Construct 3
equations starting with *x* = 2

(b) Construct 3
equations starting with *x* = − 2

(a) *x* = 2

Multiplying both sides by 5,

5*x*
= 10 (i)

Subtracting 3 from both sides,

5*x*
− 3 = 10 − 3

5 *x*
− 3 = 7 (ii)

Dividing both sides by 2,

(b) *x *= −2

Subtracting 2 from both sides,

*x*
− 2 = − 2 − 2

*x*
− 2 = −4 (i)

Again,
*x *= −2

Multiplying by 6,

6 ×
*x* = −2 × 6

6*x*
= −12

Subtracting 12 from both sides,

6*x*
− 12 = − 12 − 12

6*x*
− 12 = −24 (ii)

Adding 24 to both sides,

6*x*
− 12 + 24 = − 24 + 24

6*x*
+ 12 = 0 (iii)

**
**